Factors related to diabetic gangrene debridement service bills at Aisyiyah Hospital Bojonegoro in 2021 - Ratih Meireva Soeroso; Atik Nurwahyuni (Science Midwifery, 2023)
Diabetes mellitus is a chronic disease that cannot be cured and can cause serious complications, including diabetic gangrene. This research is a retrospective non-experimental descriptive study that aims to analyze factors related to the bill for diabetic gangrene debridement services at Aisyiyah Bojonegoro Hospital in 2021. Of the 151 patients who met the criteria, it was found that most diabetic gangrene patients who underwent debridement were aged under 60 years (66.2%), with the most sex being female (53%), and the most degree being grade 1 (51.7%). With a minimum length of stay of 2 days and a maximum length of stay of 13 days. From the results of the study, it was found that the bill was more than INA-CBGs by 37 cases at degree I, 6 cases at degree II, and 24 cases at degree III. So that from a total of 151 patients treated with diabetic gangrene debridement, there were 67 cases where hospital bills were higher (deficit) than INA-CBGs. The deficit results were found in all treatment classes and all levels of severity except in class 2 degrees I and III and in class 1 degree II where a surplus was obtained compared to INA-CBGs. Based on the results of the study, it was found that P-Value <0.05 was at the level of severity, fornas compliance, length of stay and DPJP which means that there was a significant relationship between severity, fornas compliance, length of stay, and DPJP with the total real bills of diabetic gangrene debridement patients.